Physiological stress markers during breath‐hold diving and SCUBA diving. Issue 6 (25th March 2019) - Marlinge, Marion; Coulange, Mathieu; Fitzpatrick, Richard C.; Delacroix, Romain; Gabarre, Alexie; Lainé, Nicolas; Cautela, Jennifer; Louge, Pierre; Boussuges, Alain; Rostain, Jean‐Claude; Guieu, Régis; Joulia, Fabrice C.
Abstract: This study investigated the sources of physiological stress in diving by comparing SCUBA dives (stressors: hydrostatic pressure, cold, and hyperoxia), apneic dives (hydrostatic pressure, cold, physical activity, hypoxia), and dry static apnea (hypoxia only). We hypothesized that despite the hypoxia induces by a long static apnea, it would be less stressful than SCUBA dive or apneic dives since the latter combined high pressure, physical activity, and cold exposure. Blood samples were collected from 12SCUBA and 12 apnea divers before and after dives. On a different occasion, samples were collected from the apneic group before and after a maximal static dry apnea. We measured changes in levels of the stress hormones cortisol and copeptin in each situation. To identify localized effects of the stress, we measured levels of the cardiac injury markers troponin (cTnI) and brain natriuretic peptide (BNP), the muscular stress markers myoglobin and lactate), and the hypoxemia marker ischemia‐modified albumin (IMA). Copeptin, cortisol, and IMA levels increased for the apneic dive and the static dry apnea, whereas they decreased for the SCUBA dive. Troponin, BNP, and myoglobin levels increased for the apneic dive, but were unchanged for the SCUBA dive and the static dry apnea. We conclude that hypoxia induced by apnea is the dominant trigger for the release of stress hormones and cardiac injury markers, whereas cold or and hyperbaric exposures play a minor role. These results indicate that subjects should be screened carefully for pre‐existing cardiac diseases before undertaking significant apneic maneuvers. Abstract : This study investigated the sources of physiological stress in diving by comparing SCUBA dives, apneic dives, and dry static apnea. We conclude that hypoxia is the dominant trigger for the release of stress hormones and cardiac injury markers, whereas cold or and hyperbaric exposures play a minor role. These results indicate that subjects should be screened carefully for pre‐existing cardiac diseases before undertaking significant apneic maneuvers.